2022
DOI: 10.1371/journal.pone.0264650
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte sodium buffering capacity status correlates with self-reported salt intake in a population from Livingstone, Zambia

Abstract: Background Salt impairs endothelial function and increases arterial stiffness independent of blood pressure. The mechanisms are unknown. Recent evidence suggests that there is a possible link between salt consumption and sodium buffering capacity and cardiovascular disease but there is limited evidence in the populations living in Sub-Saharan Africa. The aim of our study was to explore the relationship between erythrocyte sodium buffering capacity and sociodemographic, clinical factors, and self-reported salt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…Nevertheless, hemolytic reactions still occur despite the accurate performance of standard methods of blood group detection [2]. The analysis of electrophoretic mobility (EM) of red blood cells (RBCs) reflects the presence of a negative charge on erythrocyte [3, 4] and is reduced after the treatment with the antibody, as was first demonstrated by Coulter [5] and after the addition of Coomb's reagent [6]. The first antibody is unable to project beyond the glycocalyx of the cell and causes a significant decrease in the negative charge [7].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, hemolytic reactions still occur despite the accurate performance of standard methods of blood group detection [2]. The analysis of electrophoretic mobility (EM) of red blood cells (RBCs) reflects the presence of a negative charge on erythrocyte [3, 4] and is reduced after the treatment with the antibody, as was first demonstrated by Coulter [5] and after the addition of Coomb's reagent [6]. The first antibody is unable to project beyond the glycocalyx of the cell and causes a significant decrease in the negative charge [7].…”
Section: Introductionmentioning
confidence: 99%
“…From the insterstitium sodium diffuses into the intestinal capillaries for transport. In the vasculature, excess dietary salt diminishes the buffering capacity of the negatively charged glycocalyx lining the endothelium and the red blood cells leading to extravasation of sodium and accumulation of salt in the interstitial tissues ( 140 , 155 , 156 ). Accumulation of salt in the skin increases the density and hyperplasia of the lymph-capillary network and this effect is mediated by activation of tonicity-responsive enhancer binding protein (TonEBP) in mononuclear phagocyte system (MPS) cells ( 140 ).…”
Section: Dietary Salt In Hypertensive Heart Disease and Its Complicat...mentioning
confidence: 99%
“…It is not clear how much sodium is required to degrade the glycocalyx. However, a recent study indicates that high sodium consumption was accompanied by poor red blood cell sodium sensitivity, which implies a deteriorated glycocalyx [11]. Recently, our laboratory demonstrated that 12-weeks of high-sodium diet in mice deteriorates the endothelial glycocalyx [12 && ] and induces arterial dysfunction, indicated by elevated systolic blood pressure, aortic stiffening, and endothelial dysfunction [13].…”
Section: High-salt Dietmentioning
confidence: 99%